Pemanfaatan Cangkang Kerang Darah (Anadara granosa) Sebagai Filter Terhadap Kinerja Produksi dan Respons Fisiologi Benih Ikan Jelawat (Leptobarbus hoeveniii Blkr) - Eko Harianto; Muarofah Ghofur; Satria Panuntun; Safratilofa Safratilofa (Universitas Batangahari Jambi, 2023)
This study aims to determine the best shell particle size as a filter for recirculation systems in the rearing of barramundi (Leptobarbus hoevenii, Blkr) on production performance and physiological response. The study was conducted using an environmental design in a completely randomized design with 4 treatments and 3 replications, including treatment of without the addition of blood clam shells (A), size of the blood clam shell is 1 mm (B), size of the blood clam shell is 2 mm (C) and size of the blood clam shell is 1 mm 3 mm (D). The fish used in this study were the fingerlings of 2 ± 0.2 inches in size. The research results show that survival rates for all treatments ranged from 81.19% - 84.52%, specific weight growth rates for all treatments ranged from 4.01%/day - 4.24%/day, absolute length growth for all treatments ranged from 1.53 cm - 1.84 cm, absolute weight growth for all treatments ranged from 0.95 g - 1.08 g, feed conversion ratio for all treatments ranged from 2.51 - 2.98 and the coefficient of variation in final weight for all treatments ranged from 20.69 % - 24.84 %. Blood glucose values at the end of the maintenance period ranged from 56.67 mg/dL – 95.67 mg/dL. The results of the analysis of the water quality of the rearing medium show that the water quality is still in the feasible range for the maintenance of barnet fish